The role of the English language in the tourism industry - Rao, Ravantharanathe; Abdullah, Syaharom (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
The Malaysian government has designated 2007 as visit Malaysia year. The country is expected to attract more than 20 million visitors and earn about RM50 billion from tourism related activities. An important component in the tourism industry is the human resource. The human resource factor plays an eminent role in promoting the image of the country as a top tourism spot. Tourists do not just come for the facilities and attractions. They want to be treated right and well. A good command of the English language is always regarded as an asset for personnel in the tourism industry since most visitors do not speak Bahasa Melayu, the national language. However, the preference for those with good English proficiency will burden the recruitment of hotel personnel. This paper will present the findings of a study conducted employing the questionnaire survey and interview methods to investigate the relative role of English language proficiency in the choice of holiday destination. It was found that the role of English language proficiency in the tourism industry is prominent. It is a factor that could affect choice of hotel and satisfaction of stay. However, the results obtained indicate that the role and importance of the English language in the tourism industry is relative to job function.